Shaping the Future: Ten Years of the Occupational Health Internship Program. (August 2013) - Delp, Linda; Riley, Kevin; Jacobs, Sarah; Bush, Diane; Kirkland, Katherine; Denis, Ingrid; London, Matt; Harrison, Robert
The Occupational Health Internship Program (OHIP) was initiated in 2003 to recruit a new, diverse generation of occupational safety and health (OSH) professionals and to advance OSH within union and community-based initiatives. It retains the principles of the original OCAW/Montefiore internship program while adapting to the changed landscape of the 21st-century workplace. Case studies of OHIP projects illustrate how students have contributed to key OSH policies—to regulate silica exposure among construction workers, apply principles of green chemistry with Vietnamese nail salon workers, and integrate OSH into "green" jobs in the recycling industry. They have supported innovative campaigns with immigrant workers in contingent jobs—from taxi drivers to warehouse workers. The students, in turn, have been inspired to enter the OSH arena as professionals and worker advocates with the potential to contribute new energy to an OSH movement.